Six-Minute-Walk Test Follow-Up In Post-Coronavirus Disease 2019 Patients - Gencer, Ayşegül; Öztürk, Buket Çalışkaner; Atahan, Ersan; Gemicioğlu, Bilun (Cerrahpaşa Medical Journal, 2024)
Objective: Since coronavirus disease 2019 (COVID-19) is a novel disease that involves the respiratory system, its long-term effect on respiratory functions is not exactly known. The complaint of dyspnea may contain for a long term in the patients with COVID-19. In this study, consecutive 6-minute-walk-test (6MWT) walking distance, spirometry and radiological findings of patients who continued to complain of dyspnea after COVID-19 were evaluated at the first and third months. Methods: Two visits were performed at the first and third months in 34 patients with complaints of dyspnea in the post-COVID-19 period. Six-minutewalk-test and spirometry were performed. The Borg scale was used to evaluate dyspnea and leg fatigue before and after 6MWT. COVID-19 lesions in the lung parenchyma detected by thoracic computed tomography (CT) in the acute stage were divided into three groups using visual quantities as 50% involvement. The patients were grouped and compared according to lung involvement percentages in the thoracic CT scan. Results: Thirty-four (27 females and 7 males) patients were included into this study. Six-minute-walk-test score was significantly higher in the third month than in the first month (P = .001). Similarly, 6MWT score was significantly higher in the third month than in the first month in the patients with <30% lung involvement (P = .005). There was no statistically significant difference was found between the spirometry values (FEV1, FVC, FEV1/FVC) of the different radiological involvement groups. Conclusion: It was observed that the 6MWT distance of the patients increased in the third month, and the walking distance increased more in the third month in patients with less lung involvement. However, no difference was detected between spirometry values according to radiological groups. 6MWT is easily accessible and easily implemented. It may be considered for follow-up of patients after COVID-19. Cite this article as: Gencer A, Çalışkaner Özturk B, Atahan E, Gemicioğlu B. Six-minute-walk test follow-up in post-coronavirus disease 2019 patients. Cerrahpaşa Med J. 2024;48(1):19-25.